Recurrent respiratory infections between immunity and atopy. (3rd February 2020) - Cuppari, Caterina; Colavita, Laura; Miraglia Del Giudice, Michele; Chimenz, Roberto; Salpietro, Carmelo
Abstract: Recurrent respiratory infections (RRIs) are frequent in children and are characterized by more than 6 airway infections in 1 year or more than 1 upper airway infection per month in the period between September and April or more than 3 lower airway infections in 1 year. Often pediatric RRIs are related to predisposing factors, such as reduced airway size, poor tussive reflex, and immaturity of the immune system. RRIs due to immature immune system are a transient condition, with spontaneous resolution in the school age. However, some RRIs are expression of more complex diseases. Red flags are the onset of symptoms in the first year of life, the involvement of other systems, unusual pathogens, slowing of growth, severe infections of the lower airways, and recurrence of the infection site. To help the pediatrician in the RRI differential diagnosis, we have created a roadmap based on scientific literature data and clinical practice that identifies 6 macro areas: immunodeficiencies, simple minimal genetic immunodeficiency, atopy, obesity, nutritional deficiencies, autoinflammatory diseases, and complex diseases.